Perancangan Sistem Informasi Akuntansi Laporan Perhitungan Hasil Usaha - Dony Waluya Firdaus; Lina Rahmawati (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2018)
This research was conducted by the researcher in the research organization of the High School 2. has been computerized using Microsoft Excel, but not in accounting standards such as ledgers, books large, balance sheets, operating reports and calculation results. Report on Accounting Information System Design Calculation Results of Operations in Residents of Vocational School 2 Bandung Using PHP and MySQL. Where data becomes input data for members, savings, loan applications, loan payments and payment of cooperative operating costs. Descriptive analytical research and survey research design using quantitative. The system development method used is iteration. The used starts system context model context, data flow diagrams and data dictionaries, document flow charts, normalization and entity relationship diagrams. The results of this study will be general journals, ledgers, trial balance calculations and report on the results of operations.